Synthesis of 6‐Fluoro‐7‐cyclic Amino‐substituted Dicarboxylic Acid Quinolones and their Antibacterial Activity. (18th April 2014) - Ravi Kumar, A.; Sathaiah, G.; Chandra Shekhar, A.; Raju, K.; Shanthan Rao, P.; Narsaiah, B.; Kanaka Raju, Y.; Murthy, U. S. N.; Srimai, V.; Ramesh, M.; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> Novel 1‐carboxymethyl‐6‐fluoro‐7‐cyclic amino‐substituted‐4‐oxo‐1, 4‐dihydroquinolone‐3‐carboxylic acids 7a, 7b, 7c, 7d, 7e, 7f, 7g, 7h, 7i, 7j, 7k, 7l, 7m, 7n were synthesized as a new class of quinolones. Ethyl‐6‐fluoro‐7‐chloro‐1, 4‐dihydro‐4‐quinoline‐3‐carboxylic acid was prepared from conventional method and reacted with ethyl bromoacetate to furnish N‐carboxymethyl derivatives. The compounds were screed against various Gram‐positive and Gram‐negative bacterial strains. Antibacterial activity data is validated by molecular docking studies.